Competing patriarchal and feminist discourses in selected films of Tahmineh Milani - Feizabadi, Anna Sadat (2014)
The present study explores patriarchal and feminist discourses and the impact of patriarchal dominance that exists in Iranian culture in two of the feminist director Tahmineh Milani‘s more acclaimed films, namely Two Women (1999) and Ceasefire (2006). The ways in which male and female characters are verbally and visually represented in these movies will be examined to reveal the nuances of gender discourse and constructed identities, in terms of power and social relations. This is significant because films influence the construction of gender identity for both men and women; and to overlook this significance runs the risk of perpetuating centuriesold pattern of oppression. Norman Fairclough‘s (1995) three-dimensional model of critical discourse analysis (CDA) will be applied to the two Milani films, so as to explore the relationship between discourse and society, text and context, and particularly language and power—due to the fact that the ideological properties of language make it a central component of power, and thereby a force in moulding an individual‘s social and cultural identities. Accordingly, three dimensions of analysis will be carried out, including the description of text, the interpretation of the relationship between elements of the text, and the interaction and explanation of the relationship between interaction and social context. The findings reveal that two discourses are at play in the films: that of patriarchy/control, which is constructed in the verbal and visual language of the male characters; and the discourse of feminism/liberation, which is manifested in the verbal and visual language of female characters. The objectification of women, verbal abuse, physical violence, and the narrative of male superiority are the elements that constitute the discourse of patriarchy, while the subjugation of women, in terms of the denial of education, employment, independence, sisterhood, and equal power relations form the discourse of feminism. The results also reveal that patriarchy is the more dominant ideology and discourse in Iran that is both manifested and ratified at the family, legal, political and societal levels, and the agents of this discourse attempt to exercise power on the agents of the discourse of feminism. In terms of depiction of women, the results of the analysis reveal that Milani‘s greatest concern is the subjectification and liberation of women, through her representations of educated, independent women who struggle for their subject position in family and society, and also for equal relations and rights with men.